A method for preparing a five-layer symmetrical solid oxide battery
By adopting a five-layer structure symmetrical cell skeleton in the solid oxide fuel cell and utilizing the through-hole structure and electrolyte layer of 3YSZ and SSZ, the problems of low electrochemical performance and high ohmic impedance of traditional SOFC are solved, and a more efficient gas Diffusion and electrochemical performance improvements.
Patent Information
- Application Number
- CN202410847098.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-06-27
AI Technical Summary
Traditional symmetric solid oxide fuel cells (SOFCs) have low electrochemical properties and high ohmic impedance due to compatibility problems between the electrode and the electrolyte.
Using the preparation method of a five-layer structure symmetrical solid oxide battery, using 3YSZ with high mechanical strength as the support layer, combined with the double-layer phase inversion cast 3YSZ/SSZ straight hole support body, 3YSZ straight hole|SSZ straight hole|| SSZ electrolyte||SSZ straight hole|3YSZ straight hole's five-layer symmetrical structural skeleton enhances gas diffusion and reduces the thickness of the electrolyte.
It effectively enhances the diffusion of gas in the pores, reduces ohmic impedance, improves the electrochemical performance of the battery, and at the same time ensures the mechanical strength of the battery.
Smart Images

Figure CN118888802B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid oxide fuel cells (SOFCs), and specifically refers to a method for preparing a five-layer symmetrical solid oxide battery. Background Art
[0002] Solid oxide fuel cell (SOFC) is an energy conversion device that can directly convert chemical energy into electrical energy. The cathode and anode of traditional SOFC are composed of different materials. The battery of this structure is not only complicated in preparation process, but also has compatibility problems of phase interface (cathode / electrolyte interface and anode / electrolyte interface) at the triple phase boundary (TPB). Someone proposed a SOFC (symmetrical solid oxide fuel cell (SSOFC)) in which both the anode and cathode are made of the same material. Compared with the traditional SOFC, the same material is used as the electrode, which simplifies the preparation process of the battery and reduces the compatibility problem between the electrode and the electrolyte. In addition, switching the cathode and cathode gases can eliminate the degradation of battery performance caused by carbon deposition. However, traditional SSOFC usually adopts an electrolyte-supported structure. Because the battery requires a certain strength, the electrolyte is thicker, the ohmic impedance is higher, and the electrochemical performance of the battery is lower. In order to further improve the performance of the battery, an electrode-supported SSOFC battery structure is proposed. A certain amount of pore-forming agent is added during the preparation of the support body of the electrode-supported battery, such as starch, graphite and carbon powder. The formation of pores is conducive to the transmission of gas. Since the pores made by traditional pore-forming agents are irregular and have poor permeability, they will seriously hinder gas diffusion, resulting in poor battery performance. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a five-layer symmetrical solid oxide battery. The solid oxide battery prepared by this method can effectively enhance the diffusion of gas in the pores, increase the electrochemical performance of the battery, and can greatly reduce the thickness of the electrolyte and reduce the ohmic impedance. The preparation process is simple.
[0004] To achieve the above object, the present invention provides a method for preparing a five-layer symmetrical solid oxide battery, comprising the following steps:
[0005] S1: preparing solution I: adding solvent N-methyl-2-pyrrolidone, binder polyethersulfone, and dispersant polyvinylpyrrolidone K-30 into a ball mill according to a certain mass ratio, adding an appropriate amount of zirconium beads into the ball mill, and planetary ball milling for 24 hours to obtain solution I;
[0006] S2: preparing phase inversion 3YSZ tape casting slurry: adding 3YSZ powder and solution I into a ball mill according to the mass ratio, adding an appropriate amount of zirconium beads into the ball mill, ball milling for 20 h in a rolling ball mill, then adding 3% to 5% of graphite by weight of the powder into the ball mill, and finally ball milling for 1 h to obtain phase inversion 3YSZ tape casting slurry;
[0007] S3: preparing phase inversion SSZ tape casting slurry: adding SSZ powder and solution I into a ball mill according to the mass ratio, adding an appropriate amount of zirconium beads into the ball mill, ball milling for 20 h in a rolling ball mill, then adding 30% graphite and starch by weight of the powder into the ball mill, and finally ball milling for 1 h in the ball mill to obtain phase inversion SSZ tape casting slurry;
[0008] S4: The two slurries obtained in step S2 and step S3 are treated in a vacuum pump for 30-40 minutes. First, the 3YSZ slurry is cast on a glass plate with a knife height of 1000 μm, and then the SSZ slurry is cast on the 3YSZ with a knife height of 1300 μm. The glass plate is immediately placed in a water tank and converted in water for 12 hours to obtain a 3YSZ|SSZ double-layer straight hole blank I;
[0009] S5: Cut the blank I obtained in step S4 into discs with a diameter of 20 mm, and dry the cut discs in an oven at 80° C. for 3 h to obtain a dried blank II;
[0010] S6: preparing SSZ electrolyte solution: putting SSZ, organic solvent, dispersant and binder into a ball milling jar, using zirconium beads as ball milling media, to obtain SSZ electrolyte solution;
[0011] S7: configure a five-layer symmetrical structure skeleton: evenly drip the SSZ electrolyte solution obtained in step S6 on the SSZ skin layers of two circular blanks II, then put the SSZ skin layers of the two blanks II face to face, press them with a weight of 2 kg, dry them in an oven at 80°C for 15 minutes, and then sinter them in a high-temperature furnace at 1300°C for 4 hours to obtain a five-layer symmetrical structure skeleton of 3YSZ straight hole|SSZ straight hole||SSZ electrolyte||SSZ straight hole|3YSZ straight hole;
[0012] S8: Prepare the impregnation solution Pr 0.6 Ba 0.1 Sr 0.3 Fe 0.8 Ni 0.2 O 3-δ(PBSFN): Prepare 0.2 mol / L impregnation solution. First, dissolve the stoichiometric ratio of Pr(NO3)3·6H2O, Sr(NO3)2, Ba(NO3)2, Fe(NO3)3·9H2O, and Ni(NO3)3·6H2O in an appropriate amount of water, add 5% polyvinylpyrrolidone K-30 of the total mass of nitrate, and finally add glycine, wherein the molar ratio of glycine to nitrate in the impregnation solution is 1:1, and stir continuously until it is completely dissolved;
[0013] S9: Preparation of five-layer SSOFC: The impregnation liquid of step S8 is impregnated into the five-layer symmetrical structure skeleton obtained in step S6 in small amounts and multiple times. Each impregnation should be sintered at 450°C for 2 hours. Weigh until it reaches 14% of the mass of the battery skeleton, and then sintered at 850°C for 2 hours to obtain a five-layer SSOFC of 3YSZ-PBSFN|SSZ-PBSFN||SSZ||SSZ-PBSFN|3YSZ-PBSFN after impregnation.
[0014] As a further solution of the invention: in step S1, the mass ratio of the solvent, the binder and the dispersant is 20:4:0.35.
[0015] As a further aspect of the invention: the mass ratio in step S2 is 1:0.46.
[0016] As a further solution of the invention: the mass ratio in step S3 is 1:0.46, and the mass ratio of graphite to starch is 1.61.
[0017] As a further solution of the invention: after step S9, a slurry with higher conductivity is poured into the ceramic support, including one or a combination of precious metals Ag, Au, Pd; or a perovskite oxide slurry with higher conductivity, and the perovskite oxide is stable in hydrogen and has good chemical compatibility with 3YSZ and SSZ.
[0018] As a further solution of the present invention: the 3YSZ is 3% Y2O3 doped ZrO2, the molecular formula Y 0.058 Zr 0.942 O 1.971 , the SSZ is Sc stabilized ZrO2, the molecular formula is Sc 0.18 Zr 0.82 O 1.91 .
[0019] As a further solution of the present invention: the five-layer symmetrical structure skeleton formed in step S7, wherein the 3YSZ layer is a through-hole structure of 40 to 60 μm, and the SSZ layer is a through-hole structure of 5 to 20 μm.
[0020] As a further solution of the present invention, the small pores on the surface of the SSZ layer in contact with the SSZ electrolyte layer serve as a three-phase reaction interface between the impregnated particles and the electrolyte.
[0021] Compared with the prior art, the present invention adopts 3YSZ with high mechanical strength as the support layer, and uses a double-layer phase conversion tape-cast 3YSZ / SSZ straight hole support body, and then combines the tape-casting and co-sintering process to prepare a 5-layer symmetrical structure SSOFC. The battery skeleton is a five-layer symmetrical structure skeleton of 3YSZ straight hole|SSZ straight hole||SSZ electrolyte||SSZ straight hole|3YSZ straight hole; the symmetrical straight hole structure of the skeleton can effectively enhance the diffusion of gas in the pores, reduce the tortuosity of the pores in the structure, and reduce the gas diffusion resistance, thereby increasing the electrochemical performance of the battery; the electrode-supported SSOFC can greatly reduce the thickness of the electrolyte, reduce the ohmic impedance, and improve the electrochemical performance of the battery; the straight hole using 3YSZ as the support can effectively ensure the mechanical strength of the battery. In addition, the present invention can obtain straight holes with a straight hole diameter ranging from 5 to 60 μm through process control. The process of the present invention is simple, which is conducive to the production and commercial application of large-size batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 (a) is a schematic diagram of the cross-sectional structure of the five-layer symmetrical structural skeleton of 3YSZ straight pore | SSZ straight pore || SSZ electrolyte || SSZ straight pore | 3YSZ straight pore of the present invention.
[0023] Figure 1 (b) Cross-sectional view of 3YSZ porous||SSZ electrolyte||3YSZ porous symmetric skeleton prepared by traditional pore formers.
[0024] Figure 2 It is a skeleton plan view of the five-layer symmetrical structure of the present invention.
[0025] Figure 3 It is the performance of the five-layer symmetrical battery of the present invention under hydrogen. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with the accompanying drawings.
[0027] A method for preparing a five-layer symmetrical solid oxide battery comprises the following steps:
[0028] S1: preparing solution I: adding solvent N-methyl-2-pyrrolidone, binder polyethersulfone, and dispersant polyvinylpyrrolidone K-30 into a ball mill in a mass ratio of 20:4:0.35, adding an appropriate amount of zirconium beads into the ball mill, and planetary ball milling for 24 hours to obtain solution I;
[0029] S2: preparing phase inversion 3YSZ tape casting slurry: adding 3YSZ powder and solution I into a ball mill at a mass ratio of 1:0.46, adding an appropriate amount of zirconium beads into the ball mill, ball milling for 20 h in a rolling ball mill, then adding 3% to 5% of graphite by weight of the powder into the ball mill, and finally ball milling for 1 h to obtain phase inversion 3YSZ tape casting slurry;
[0030] S3: preparing phase inversion SSZ tape casting slurry: adding SSZ powder and solution I into a ball mill at a mass ratio of 1:0.46, adding an appropriate amount of zirconium beads into the ball mill, and ball milling for 20 hours in a rolling ball mill, and then adding 30% graphite and starch by weight of the powder into the ball mill, wherein the ratio of graphite to starch is 1.6:1, and finally ball milling for 1 hour in the ball mill to obtain phase inversion SSZ tape casting slurry;
[0031] S4: Treat the two slurries obtained in step S2 and step S3 in a vacuum pump for 30 to 40 minutes. First, cast the 3YSZ slurry on a glass plate with a knife height of 1000 μm, and then cast the SSZ slurry on the 3YSZ with a knife height of 1300 μm. Immediately put the glass plate into a water tank and convert it in water for 12 hours to obtain a 3YSZ|SSZ double-layer straight hole blank I.
[0032] S5: Cut the blank I obtained in step S4 into discs with a diameter of 20 mm, and dry the cut discs in an oven at 80° C. for 3 h to obtain a dried blank II;
[0033] S6: preparing SSZ electrolyte solution: putting SSZ, organic solvent, dispersant and binder into a ball milling jar, using zirconium beads as ball milling media, to obtain SSZ electrolyte solution;
[0034] S7: configure a five-layer symmetrical structure skeleton: evenly drip the SSZ electrolyte solution obtained in step S6 on the SSZ skin layers of two circular blanks II, then put the SSZ skin layers of the two blanks II face to face, press them with a weight of 2 kg, dry them in an oven at 80°C for 15 minutes, and then sinter them in a high-temperature furnace at 1300°C for 4 hours to obtain a five-layer symmetrical structure skeleton of 3YSZ straight hole|SSZ straight hole||SSZ electrolyte||SSZ straight hole|3YSZ straight hole;
[0035] S8: Prepare the impregnation solution Pr 0.6 Ba 0.1 Sr 0.3 Fe 0.8 Ni 0.2 O 3-δ(PBSFN): Prepare 0.2 mol / L impregnation solution. First, dissolve the stoichiometric ratio of Pr(NO3)3·6H2O, Sr(NO3)2, Ba(NO3)2, Fe(NO3)3·9H2O, and Ni(NO3)3·6H2O in an appropriate amount of water, add 5% polyvinylpyrrolidone K-30 of the total mass of nitrate, and finally add glycine, wherein the molar ratio of glycine to nitrate in the impregnation solution is 1:1, and stir continuously until it is completely dissolved;
[0036] S9: Preparation of five-layer SSOFC: The impregnation liquid of step S8 is impregnated into the five-layer symmetrical structure skeleton obtained in step S6 in small amounts and multiple times. Each impregnation should be sintered at 450°C for 2 hours. Weigh until it reaches 14% of the mass of the battery skeleton, and then sintered at 850°C for 2 hours to obtain a five-layer SSOFC of 3YSZ-PBSFN|SSZ-PBSFN||SSZ||SSZ-PBSFN|3YSZ-PBSFN after impregnation.
[0037] In order to improve the electron conductivity on the anode side and conduct the electrons generated at the three-phase interface, a slurry with high conductivity, such as precious metals Ag, Au, Pd, or a perovskite oxide slurry with high conductivity, needs to be poured into the ceramic support body. The perovskite oxide is stable in hydrogen and has good chemical compatibility with 3YSZ and SSZ. The ceramic support body refers to the five-layer SSOFC except the electrolyte.
[0038] 3YSZ is 3% Y2O3 doped ZrO2, molecular formula Y 0.058 Zr 0.942 O 1.971 SSZ is Sc stabilized ZrO2, with the molecular formula of Sc 0.18 Zr 0.82 O 1.91 , all are commercial powders.
[0039] In step S6, the organic solvent is butyl acetate, the dispersant is DM55, the binder is b50 and b72, and the mass ratio of SSZ, organic solvent, dispersant and binder is 20:60:4:6, wherein the sum of b50 and b72 accounts for 6. Since the electrolyte solution is configured, the electrolyte layer of the battery of the present invention is very thin, which reduces the ohmic impedance and improves the electrochemical performance of the battery.
[0040] The five-layer symmetrical structural skeleton formed in step S7, wherein the 3YSZ layer is a through-hole structure of 40 to 60 μm, and the SSZ layer is a through-hole structure of 5 to 20 μm; the symmetrical through-hole structure can effectively enhance the diffusion of gas in the pores, reduce the tortuosity of the pores in the structure, reduce the gas diffusion resistance, and thus increase the electrochemical performance of the battery.
[0041] The small pores in the SSZ surface layer in contact with the SSZ electrolyte layer can serve as a three-phase reaction interface for the impregnated particles and the electrolyte.
[0042] The five-layer symmetrical structure of the present invention was compared with the traditional skeleton by SEM. Figure 1 As shown, Figure 1 (a) is a cross-sectional view of the five-layer symmetrical structural skeleton of 3YSZ straight pore|SSZ straight pore||SSZ electrolyte||SSZ straight pore|3YSZ straight pore of the present invention, Figure 1 (b) is a cross-sectional view of the 3YSZ porous||SSZ electrolyte||3YSZ porous symmetrical skeleton prepared by a traditional pore-forming agent. From the figure, it can be seen that the pores formed by the skeleton of the five-layer symmetrical structure of the present invention are continuous, which is conducive to gas transmission. Figure 2 This is a plan view of the skeleton of the five-layer symmetrical structure of the present invention. It can be seen from the figure that the pores are mostly 5 to 60 μm in diameter. Figure 3 The performance of the five-layer symmetrical battery of the present invention under hydrogen is shown in Figure 1. Its maximum power density is 277.2 mW / cm at 800°C. 2 .
Claims
1. A method for preparing a five-layer symmetrical solid oxide battery, characterized in that: The following steps are involved: S1: preparing solution I: adding solvent N-methyl-2-pyrrolidone, binder polyethersulfone and dispersant polyvinylpyrrolidone K-30 into a ball mill according to a certain mass ratio, adding an appropriate amount of zirconium beads into the ball mill, and planetary ball milling for 24 hours to obtain solution I; S2: preparing phase inversion 3YSZ tape casting slurry: adding 3YSZ powder and solution I into a ball mill according to the mass ratio, adding an appropriate amount of zirconium beads into the ball mill, ball milling for 20 h in a rolling ball mill, then adding 3% to 5% of graphite by weight of the powder into the ball mill, and finally ball milling for 1 h to obtain phase inversion 3YSZ tape casting slurry; S3: preparing phase inversion SSZ tape casting slurry: adding SSZ powder and solution I into a ball mill according to the mass ratio, adding an appropriate amount of zirconium beads into the ball mill, ball milling in a rolling ball mill for 20 h, then adding 30% graphite and starch by weight of the powder into the ball mill, and finally ball milling in the ball mill for 1 h to obtain phase inversion SSZ tape casting slurry; S4: The two slurries obtained in step S2 and step S3 are treated in a vacuum pump for 30-40 min. First, the 3YSZ slurry is cast on a glass plate with a knife height of 1000 μm, and then the SSZ slurry is cast on the 3YSZ with a knife height of 1300 μm. The glass plate is immediately placed in a water tank and converted in water for 12 h to obtain a 3YSZ|SSZ double-layer straight hole blank I; S5: Cut the blank I obtained in step S4 into discs with a diameter of 20 mm, and place the cut discs on a 80 o C in an oven for 3 h to obtain a dry embryo II; S6: preparing SSZ electrolyte solution: putting SSZ, organic solvent, dispersant and binder into a ball milling jar, using zirconium beads as ball milling media, to obtain SSZ electrolyte solution; S7: Configuring a five-layer symmetrical skeleton: Evenly apply the SSZ electrolyte solution obtained in step S6 to the SSZ skin layers of the two circular blanks II, and then put the SSZ skin layers of the two blanks II face to face together, press them with a weight of 2 kg, and press them at 80 o After drying in an oven at 1300 °C for 15 min, o C high temperature furnace sintering for 4h, a five-layer symmetrical structural skeleton of 3YSZ straight hole|SSZ straight hole||SSZ electrolyte||SSZ straight hole|3YSZ straight hole was obtained; S8: Prepare the impregnation solution Pr 0.6 Ba 0.1 Sr 0.3 Fe 0.8 Ni 0.2 O 3-δ (PBSFN): Prepare 0.2 mol / L impregnation solution. First, dissolve the stoichiometric ratio of Pr(NO3)3·6H2O, Sr(NO3)2, Ba(NO3)2, Fe(NO3)3·9H2O, and Ni(NO3)3·6H2O in an appropriate amount of water, add 5% polyvinylpyrrolidone K-30 of the total mass of nitrate, and finally add glycine. The molar ratio of glycine to nitrate in the impregnation solution is 1:
1. Stir continuously until it is completely dissolved. S9: Preparation of five-layer SSOFC: The impregnation solution of step S8 is impregnated into the five-layer symmetrical structure skeleton obtained in step S7 in small amounts and multiple times, and each impregnation is performed at 450 o C for 2 h, weigh until the battery skeleton mass is 14%, and then sinter at 850 o C was sintered for 2 h to obtain a five-layer SSOFC of 3YSZ-PBSFN|SSZ-PBSFN||SSZ||SSZ-PBSFN|3YSZ-PBSFN after impregnation; The 3YSZ is 3% Y2O3 doped ZrO2, with the molecular formula Y 0.058 Zr 0.942 O 1.971 , the SSZ is Sc stabilized ZrO2, the molecular formula is Sc 0.18 Zr 0.82 O 1.91 .
2. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1, characterized in that: In step S1, the mass ratio of the solvent, the binder, and the dispersant is 20:4:0.
35.
3. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1, characterized in that: The mass ratio in step S2 is 1:0.
46.
4. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1, characterized in that: The mass ratio in step S3 is 1:0.46, and the mass ratio of graphite to starch is 1.6:
1.
5. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1, characterized in that: After step S9, a slurry with high conductivity is poured into the ceramic support, wherein the slurry includes one or a combination of precious metals Ag, Au, Pd; or a perovskite oxide slurry with high conductivity, and the perovskite oxide is stable in hydrogen and has good chemical compatibility with 3YSZ and SSZ.
6. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1, characterized in that: The five-layer symmetrical structure skeleton formed in step S7 has a 3YSZ layer with a through hole structure of 40-60 μm and a SSZ layer with a through hole structure of 5-20 μm.
7. The method for preparing a five-layer symmetrical solid oxide battery according to claim 1 or 5, characterized in that: The small pores in the SSZ surface layer in contact with the SSZ electrolyte layer serve as a three-phase reaction interface for the impregnated particles and the electrolyte.
Citation Information
Patent Citations
Solid oxide fuel cell composite cathode and preparation method thereof
CN102683722A
Method for preparing solid oxide electrolytic tank through continuous reel-to-reel water system tape casting
CN115498229A